THE ROLE OF MORPHOLOGICAL AWARENESS AND EXPLICIT MORPHOLOGICAL INSTRUCTIONS IN ELT - Isvanelly Anwar; Rusdi Noor Rosa (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2020)
As a branch of linguistics, the role of morphology in learning English should not be taken carelessly. As the study of internal structure of words, morphology provides a lot of knowledge necessary to develop students’ English proficiency. However, many English teachers are still not aware of its important role in successful and effective learning process because they tend to be busy searching for media, strategies or techniques which they consider effective in teaching. In relation to the importance of morphology in English language teaching (ELT), this paper aims at explaining the important role of morphological awareness and instructions in teaching English as a foreign language to junior high schools in Indonesia. This is a descriptive study using literature review as the method. The data were secondary data in the form of documents including articles, journals and books. The data were analyzed using a content analysis by reading and reviewing the documents. The results of the data analysis show the significant role of morphological awareness and morphological instructions in facilitating the students at junior high school to learn English more easily, with significantly greater achievement. It is, therefore, concluded that students with morphological awareness or students that are treated by using morphological instruction gain better achievements in their English learning, resulting in their better English proficiency.